Trend, burden and determinants of undiagnosed hypertension in the Horn of Africa: A systematic review and meta-analysis. - Muluken Chanie Agimas; Nebiyu Mekonnen Derseh; Fantu Mamo; Moges Tadesse Abebe; Tilahun Yemanu; Meron Asmamaw (PLoS ONE)
Background Hypertension is a silent killer disease and the global report revealed that half of the world's population lives with undiagnosed hypertension. The problem is expected to be worse in low-income countries such as in Horn of Africa countries. Thus, we planned to determine the trend, burden, and determinates of undiagnosed hypertension in this region and provide conclusive and tangible evidence for interventions. Method Articles were searched on Google, Google Scholar, PubMed/Medline, EMBASE, SCOPUS, and the published articles' reference list. The JBI critical appraisal checklist was used for quality assessment. A sensitivity test and I2 statistics were conducted to evaluate the heterogeneity. The Begg's statistics in the random effect model were done to evaluate the publication bias. Result The pooled prevalence of undiagnosed hypertension in the Horn of Africa was 17% (95% CI: 15%-20%) and it ranges from from 13% in 2006 to 20% in 2023. A trip time to a medical institution of less than 35 minutes (OR = 0.52, 95%CI: 0.35-0.79), no regular exercise (OR = 2.26, 95% CI: 1.54-3.32), age > = 45 years (OR = 2.51, 95% CI: 1.66-3.8), age 35-44 years (OR = 1.88, 95% CI: 1.5-2.37), male (OR = 1.72, 95% CI: 1.34-2.2), poor knowledge (OR = 3.29, 95%CI: 2.39,4.53), normal BMI (OR = 3.84, 95% CI: 2.96-4.98), Overweight (OR = 1.97, 95% CI: 2.96-4.98), poor health seeking (OR = 2.79, 95%CI: 2.01-3.86), low vegetable consumers (OR = 1.99, 95%CI:1.36-2.91), smoking (OR = 1.47, 95%CI: 1.13-1.93), high triglyceride (OR = 1.83, 95%CI:1.33-2.52), chat chewing (OR = 2.18, 95%CI: 1.54-3.09), and alcohol drinking (OR = 1.75, 95%CI: 1.32-2.33) were the determinats of undiagnosed hypertension. Conclusion and recommendation The pooled prevalence of undiagnosed hypertension was low in the Horn of Africa but its trend was increased over time. Individual level variables were identified that affect the undiagnosed hypertension. Therefore, healthy lifestyle is recommended.